Subcellular localization and activation of ADAM proteases in the context of FasL shedding in T lymphocytes. Issue 2 (June 2015) - Ebsen, Henriette; Lettau, Marcus; Kabelitz, Dieter; Janssen, Ottmar
Highlights TCR/CD3/CD28-stimulation results in the release of soluble FasL from human T cells. FasL shedding by ADAM10 and ADAM17 is prevented by inhibition of Src kinases. Both proteases and FasL are detectable in intracellular lysosomal compartments. Without stimulation, ADAM10 and ADAM17 are not found in lipid raft platforms. An activation-induced raft positioning of the proteases results in FasL shedding.